Effect of Hard Skills, Soft Skills, Organizational Learning and Innovation Capability on Islamic University Lecturers’ Performance - Purwanto, Agus; Santoso, Priyono Budi; Siswanto, Edy; Hartuti, Hartuti; Setiana, Yuni Nuraeni; Sudargini, Yuli; Fahmi, Khaerul (International Journal of Social and Management Studies, 2021)
The purpose of this research was to measure the effect of hard skills, soft skills, organizational learning, and innovation capability on the lectures performance of an Islamic University in Indonesia. Data collection was done by simple random sampling to 261 population an Islamic University in Indonesia. The returned and valid questionnaire results were 244 samples. SEM method with SmartPLS 3.0 software is used for data processing. The findings of the study reveal that hard skills, soft skills, organizational learning, and innovation capability have a direct positive and significant effect on the lecturer's performance. Besides, soft skills have the greatest influence on lecturer performance among other variables. This research proposed a model for building the lecture's performance among the lecturers of an Islamic University in Indonesia through enhancing hard skills, soft skills, organizational learning, and innovation capability. This research could pave the way to improve the lecturer readiness in facing the 4.0 education era.